A CRITIQUE OF TAKFῙR TENDENCY IN BARBAHĀRI’S SHARḤ AS-SUNNAH - Nafiu Ahmed Arikewuyo (Khazanah: Jurnal Studi Islam dan Humaniora, 2023)
Takfῑr (excommunicating Muslims from Islam) has recently attracted renewed attention among Muslim scholars due to its devastating effects on Muslims. Modern Salafism is mostly accused of the trend. Hence, the present research traces the genesis of Takfῑr tendency to one of the most acceptable classical works among the modern Salafis, Sharḥ as-Sunnah of Imam Barbahāri (d. 329 A.H.). The paper is library-based and adopts the analytic method of research. The study reveals that Barbahāri is guilty of loose declaration of worthless matters as an act of apostasy. Some of the matters in which he displayed the Takfῑr tendency are differing from the Companions in any religious matter, the beatific vision of Allah in this world, the consecration of his work, treating Muslims as non-believers, and sweeping declaration of his contemporaries as an apostate. It also found the Takfῑr -laden approach of the author in his work was triggered by the nature of the heretic Jahmiyyah sect he targets. It will be out of context to apply his texts to the generality of non-Hanbali Muslims who don’t share the grave and dangerous creeds of the Jahmiyyah. This is the point where many modern Salafis who hold the work in high esteem become guilty. They adopt the letters of Barbahāri ’s texts as a general guideline for relating with their opponents, even if their religious differences are not up to the standard of the heretic Jahmiyyah